Vitamin A and D Levels in Preterm Neonates: The Relationship with Morbidities and Clinical Considerations - Hamide Barzegar; Zahra Hashemi; Roya Oboodi; Mohammad Ashkan Moslehi (Iranian Journal of Neonatology)
Background: Vitamin A and D deficiency are more prevalent in preterm neonates than in term. Preterm neonates are more susceptible to various complications and morbidities, including respiratory issues, sepsis, retinopathy of prematurity, hyperbilirubinemia, anemia, and intraventricular hemorrhage. This study aims to investigate potential relationships between vitamin A and D deficiency and neonatal morbidities. Methods: Forty-four neonates, all with gestational age less than 32 weeks or birth weight less than 1500 grams, were enrolled. Serum levels of vitamin A and D were assessed, and neonates were categorized into deficient and sufficient. Comparative analysis was conducted between groups using various statistical tests, including Chi-square test, Wilcoxon signed rank test, Kruskal-Wallis test, independent t-test, and Mann-Whitney test. Results: The mean gestational age was 30.5±1.7 weeks, and the mean birth weight was 1322.95±286.67 grams. The mean vitamin A and D levels were 20.95±9.79 µg/dl and 22.8±11.5 ng/ml, respectively. Vitamin A deficiency was observed in 19 individuals (43.2%), while 29 individuals (65.9%) exhibited vitamin D deficiency. A significant association was observed between vitamin D deficiency and both duration and type of oxygen support (p-value 0.04, 0.04). However, no significant differences were found between the two groups regarding other morbidities or vitamin A status. Conclusion: Limited studies have evaluated the association of vitamin levels with neonatal morbidities. Vitamin D deficiency is common among preterm neonates and is associated with the duration and type of respiratory support. Further investigations are warranted to explore potential links between vitamin deficiencies and various neonatal morbidities.